A randomised clinical trial comparing the outcome of trabeculectomy using triangular versus rectangular scleral flaps - Sharma, A; Das, H; Adhikari, S; Lavaju, P; Shrestha, BG (Nepalese Journal of Ophthalmology, 2010)
Background: Trabeculectomy is the standard surgical procedure for management of glaucoma. Objective: To compare the outcome of triangular and rectangular scleral flaps in trabeculectomy. Materials and methods: This study was carried out in the Department of Ophthalmology, BPKIHS, Dharan, over a period of one year. A total of 22 patients undergoing trabeculectomy were randomized to undergo either trabeculectomy with triangular scleral flap (Group A= 11 eyes) or trabeculectomy with rectangular flap (Group B =11 eyes). Outcome measurement: The parameters studied were intraocular pressure (IOP), anterior chamber depth (ACD), bleb characteristics and surgical complications. Statistics: P value of <0.05 was considered significant. All calculations were executed using SPSS 11.0 software program. Results: The age ranged between 40 to 76 years with the mean of 56.5±9.25 years. The most common preoperative diagnosis was angle closure glaucoma. The postoperative percentage of IOP reduction (Group A=68.9%; Group B=66.51%) was statically significant in both the groups (p=0.001). Trabeculectomy was almost equally effective with complete surgical success of 91% in group A, and 82% in group B (p=0.534). Final bleb scores were almost similar in both the groups with 3.27 ± 1.5 in group A and 3.36±1.21 in group B (p=0.877). Hypotony with the IOP less than 6 mmHg was found in the first post-operative day in 2 patients in Group A and in 1 in Group B. All of them improved spontaneously within a week. Conclusion: Both triangular and rectangular scleral flaps in trabeculectomy are equally effective in terms of post surgical IOP control, bleb characteristics and complications. Keywords: Trabeculectomy; glaucoma; intra ocular pressure; scleral flap DOI: 10.3126/nepjoph.v1i1.3669 Nep J Oph 2009;1(1):20-24